Diplomaszerző nemzetközi hallgatói mobilitás a Szegedi Tudományegyetemen az oktatás-statisztikai adatok tükrében = Graduate and post-graduate international students mobility at the University of Szeged in the light of education-statistical data - Győri, Ferenc (Közép-Európai Közlemények, 2018)
This paper analyzes the world-wide, international students mobility at the University of Szeged in the light of the institution’s annual educational statistics, as part of a complex research covering three universities in Hungary. International student mobility is mostly positively considered by casestudy literature: it extends its economic benefit to the host university, as well as the city, the region and the country. The University of Szeged plays a key role in Szeged’s economy. Students participating in international training offer economic benefits for both the university and the city. The number and proportion of foreign students is growing steadily, mainly in foreign-language, undivided and doctoral programs, especially in the fields of medical and health sciences. Europe is still the largest sender area, but the Asian “markets” are also expanding rapidly. 15% of all the university students in Szeged are foreigners coming from more than one hundred countries. At the same time, every third student belongs to the Hungarian minorities living in Serbia. The rapid expansion of the number of students is supported by the growth of education and training in foreign languages, especially in English and German.